1999
DOI: 10.1016/s0022-2275(20)33336-8
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA reductase regulation: use of structurally diverse first half-reaction squalene synthetase inhibitors to characterize the site of mevalonate-derived nonsterol regulator production in cultured IM-9 cells

Abstract: The activity of HMG-CoA reductase (HMGR) is tightly regulated, in part through post-transcriptional mechanisms that are mediated by nonsterol products of mevalonate metabolism. Previous reports have suggested that these mediators are derived from farnesyl pyrophosphate (FPP). Recent studies have implicated FPP hydrolysis products (e.g., farnesol), the squalene synthetase (SQS) reaction products presqualene pyrophosphate (PSQPP) and squalene, or their metabolites. To distinguish among these possible mediators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Several studies, in which zaragozic acid suppressed the non-sterol-induced rapid degradation of HMG-CoAR, have evoked some controversy (45)(46)(47). More recent studies, however, have demonstrated that zaragozic acid might directly interfere with the production or action of the nonsterol regulator (48), and that FPP was the source of the positive signal for HMG-CoAR degradation in mammals and yeast (49). These results indicate that FPP derivatives, but not presqualene pyrophosphate or derivatives of squalene, are the nonsterol regulators of HMG-CoAR degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, in which zaragozic acid suppressed the non-sterol-induced rapid degradation of HMG-CoAR, have evoked some controversy (45)(46)(47). More recent studies, however, have demonstrated that zaragozic acid might directly interfere with the production or action of the nonsterol regulator (48), and that FPP was the source of the positive signal for HMG-CoAR degradation in mammals and yeast (49). These results indicate that FPP derivatives, but not presqualene pyrophosphate or derivatives of squalene, are the nonsterol regulators of HMG-CoAR degradation.…”
Section: Discussionmentioning
confidence: 99%